Who lives downtown? Neighbourhood change in central Halifax, 1951–2011. Issue 2 (2nd April 2016) - Grant, Jill L.; Gregory, Will
ABSTRACT: The paper traces neighbourhood change in central Halifax, Canada, from 1951 to 2011 to consider how urban renewal policies and other factors may have influenced who lives downtown. In the 1950s planners advocated slum clearance and modernization to permit commercial expansion in the city centre. Subsequent decades saw central neighbourhoods decline. By the 1980s population began to rebound as planning policy increasingly promoted residential uses downtown. Over the 60 years central Halifax transitioned in character: three of the central tracts became increasingly affluent, while the fourth went from close to the city average to a low-income tract. The trajectories that neighbourhoods follow depend on several factors including societal changes, economic conditions, public policy interventions, and decisions made by other significant institutions (such as universities).